Multi-omics unveils tryptophan metabolic pathway as a key pathway influencing residual feed intake in Duroc swine - Wang, Shujie; Chen, Dong; Ji, Xiang; Shen, Qi; Yu, Yang; Wu, Pingxian; Tang, Guoqing (Frontiers in Veterinary Science, 2024)
The genetic trait of residual feed intake (RFI) holds considerable importance in the swine industry. Recent research indicates that the gut microbiota of pigs plays a pivotal role in the manifestation of the RFI trait. Nevertheless, the metabolic pathways involved in the functioning of these microorganisms remain elusive. Thus, based on the ranking of the RFI trait in Duroc pigs, the present study selected the top 10 and bottom 10 pigs as the experimental subjects. The distribution and metabolite differences of cecal microbiota were analyzed using 16S rRNA gene sequencing and liquid chromatography-tandem mass spectrometry (LC-MS/MS) techniques. The low RFI cecal group was named LRC, and the high RFI cecal group was named HRC. The results indicate that the LRC group had lower RFI, feed conversion ratio (FCR), average daily feed intake (ADFI) (P < 0.001), and thinner backfat (P < 0.05) compared with the HRC group. We simultaneously recorded the foraging behavior as well, the LRC group had a significant increase in total time spent at the feeder per day (TPD) (P < 0.05) and a significant increase in average feed intake per mins (AFI) and the number of visits to the feeder per day (NVD) compared to the HRC group (P < 0.001). Clostridium_XVIII, Bulleidia, and Intestinimonas were significantly enriched in the LRC group (P < 0.01), while Sutterella, Fusobacterium, and Bacteroides were significantly increased in the HRC group (P < 0.01). In the metabolome, we detected 390 (248 metabolites up and 142 down in the LRC compared with HRC), and 200 (97 metabolites up and 103 down in the LRC compared with HRC) differential metabolites in positive and negative ionization modes. The comprehensive analysis found that in the LRC group, Escherichia and Eubacterium in the gut may increase serotonin content, respectively.Bacteroides may deplete serotonin. We suggest that the RFI may be partly achieved through tryptophan metabolism in gut microbes. In individuals with low RFI, gut microbes may enhance feed efficiency by enhancing host synthesis and metabolism of tryptophan-related metabolites.